Key cooperative attribute-based encryption - HUANG, Luqi (Institutional Knowledge at Singapore Management University, 2024)
Attribute-based encryption (ABE) is an important technology in building access control systems with precise control and scalability. In an ABE system, there exists a private key generator (PKG) that issues all private keys. The PKG has a significant drawback referred to as the huge key management burden in large-scale user systems. To overcome this limitation, we propose a more flexible system that offers users the choice to utilize decryption keys either from the PKG or from trusted users to decrypt the ciphertext, reducing the workload of the PKG. Unfortunately, users are restricted to only receiving private keys from the PKG in most ABE schemes. Thus, our system ABE extends the ability of trusted users to generate and distribute decryption keys. Furthermore, decryption keys from trusted users possess equivalent decryption with a private key from the PKG when satisfying the cooperative access policy set by the encryptor. We define the concept of key cooperative ABE for the first time, presenting a key cooperative ABE scheme.